A case report: a 38-year-old man with vivax relapse malaria - Ayu Agung Pradnya Paramitha; I Putu Gede Putra Darmawan; Rachmawanti Agustina Fitriani (DiscoverSys Inc., 2022)
Introduction: Malaria is a parasitic disease caused by blood protozoa of the Plasmodium genus transmitted through the bite of a female Anopheles mosquito. Indonesia is still an endemic area, especially in the eastern regions. About 40% of malaria cases in the world are caused by Plasmodium vivax. Tertiana or vivax malaria can cause relapse because it has a hypnozoite stage that is dormant in the liver. This case report will discuss a case of relapse vivax malaria with thrombocytopenia. Case Illustration: A 38-year-old man came to the emergency room consciously with a fever complaint since 4 days before entering the hospital. Fever occurred throughout the body, disappeared, accompanied by chills and sweating. On the second day the fever began to decrease somewhat but the next day the fever began to increase. The patient has a history of serving in Papua and contracted malaria 3 months before entering the hospital. While in Papua, the patient worked as a supporter for the 2021 PON event and malaria treatment was not complete. A complete blood examination found thrombocytopenia and microscopic examination of thin drops of the presence of ring-shaped Plasmodium vivax. The patient is diagnosed with vivax relapse malaria. The patient was treated with antimalarial therapy with DHP 4 tablets in a day for 3 days and primaquine 2 tablets in a day for 14 days. Monitoring therapy was done on the eighth day, with microscopic examination, and the result was negative malaria plasmodium. Conclusion: This case report discusses vivax relapse malaria and proper management to irradiate the hypnozoite stage which has an important role in the recurrence phase.